2015
DOI: 10.1016/j.jff.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and angiotensin I converting enzyme (ACE) inhibitory activities of date seed protein hydrolysates prepared using Alcalase, Flavourzyme and Thermolysin

Abstract: A B S T R A C TDate seed flour was used to produce protein hydrolysates using Alcalase (AL), Flavourzyme (FL) and Thermolysin (TH). Enzymes were used individually or in combination at a constant pH and temperature. The degree of hydrolysis ranged between 11 and 14%. The molecular weights of peptides determined, using a quadrupole orthogonal time-of-flight hybrid tandem mass spectrometer, ranged from 2062.9 ± 0.0 to 116,803.8 ± 0.4 Da. AL hydrolysate showed the lowest reducing power and ABTS radical scavenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
177
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(189 citation statements)
references
References 56 publications
11
177
1
Order By: Relevance
“…Reducing power reflects the electron donating ability of antioxidant . The reducing powers of the control, HT and SFCU hydrolysates are significantly ( P < 0.5) different (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Reducing power reflects the electron donating ability of antioxidant . The reducing powers of the control, HT and SFCU hydrolysates are significantly ( P < 0.5) different (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Phenolic extracts were tested for their scavenging activity against hydroxyl radicals. The extracts were removed from their original solvent (methanol) under a stream of nitrogen and diluted in 75 mM phosphate buffer [16]. Experimental procedure and equipment parameters were the same as those described by de Camargo et al [10].…”
Section: Hydroxyl Radical Scavenging Activitymentioning
confidence: 99%
“…The 12 peptide fractions obtained by RP‐HPLC were tested for in vitro antioxidant and ACE‐inhibitory activities. The ABTS assay was found to be more sensitive than the DPPH assay, possibly because the ABTS radical is able to react with any hydroxylated aromatic compound and thus can be applied to assess the antioxidant activity of both lipophilic and hydrophilic molecules (Ambigaipalan et al, ). The F 1 –F 12 fractions (numbered in order of elution in RP‐HPLC) displayed ABTS scavenging and ACE‐inhibitory activities in the 5%–89% and 8%–70% range, respectively (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, Table 3 shows a predominance of hydrophobic (Ala, Val, Ile, Leu, Met, Phe, Pro, Gly) and aromatic (Phe, Trp, Tyr) residues (31.73% and 21.64%, respectively). Both classes of amino acid side chains can donate protons to electron-deficient radicals hence affect antioxidant activity (Silva et al, 2017); other side chains such as Met, Lys, Cys, and His have also been reported to enhance antioxidant activity (Ambigaipalan, Al-Khalifa, & Shahidi, 2015). Girgih et al (2014) indicated that the presence of hydrophobic amino acids affected antihypertensive activity positively.…”
Section: Amino Acid Composition Of Wgphmentioning
confidence: 99%